2021
DOI: 10.1186/s12995-021-00341-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term visual pathway alterations after elemental mercury poisoning: report of a series of 29 cases

Abstract: Background There are few clinical data on retinal involvement after acute exposure to high concentrations mercury and the available reports are based on a small number of patients suffering chronic exposure. The purpose of this paper is to report findings in workers acutely exposed to very high concentrations of mercury vapor with the aim of providing data on a possible direct retinal involvement. Methods Twenty-nine patients and 16 controls were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Nevertheless, 30-Hz flicker, single flash cone response and multifocal ERG and pattern ERG alterations also appeared when deeper and more extensive VF defects developed, suggesting that cone dysfunction and ganglion macular cells damage can occur secondarily, thus causing color vision impairment, mainly in the blue-yellow range using Roth 28 Hue test. In addition, prolonged latencies, and reduced amplitudes of P100 in visualevoked potentials compared to controls were found when severe VF was altered (Pastor-Idoate et al, 2021), as previously reported (El-Sherbeeny et al, 2006). In summary, although neurologic and visual pathway involvement was clear, there were also data suggesting the existence of a direct functional retinal damage and retinal participation in mercury poisoning.…”
Section: Retina Optic Nerve and Visual Alterationssupporting
confidence: 80%
See 3 more Smart Citations
“…Nevertheless, 30-Hz flicker, single flash cone response and multifocal ERG and pattern ERG alterations also appeared when deeper and more extensive VF defects developed, suggesting that cone dysfunction and ganglion macular cells damage can occur secondarily, thus causing color vision impairment, mainly in the blue-yellow range using Roth 28 Hue test. In addition, prolonged latencies, and reduced amplitudes of P100 in visualevoked potentials compared to controls were found when severe VF was altered (Pastor-Idoate et al, 2021), as previously reported (El-Sherbeeny et al, 2006). In summary, although neurologic and visual pathway involvement was clear, there were also data suggesting the existence of a direct functional retinal damage and retinal participation in mercury poisoning.…”
Section: Retina Optic Nerve and Visual Alterationssupporting
confidence: 80%
“…Some studies have reported retinal pigment epithelium (Bridges et al, 2007) and photoreceptor damage (Korbas et al, 2013). Recent evidence by Pastor-Idoate et al, from our group, showed a primary involvement in electroretinogram (ERG) of both the inner (oscillatory potentials) and outer retina, mainly reduced scotopic rod response, in a long-term group of affected patients (Pastor-Idoate et al, 2021). Nevertheless, 30-Hz flicker, single flash cone response and multifocal ERG and pattern ERG alterations also appeared when deeper and more extensive VF defects developed, suggesting that cone dysfunction and ganglion macular cells damage can occur secondarily, thus causing color vision impairment, mainly in the blue-yellow range using Roth 28 Hue test.…”
Section: Retina Optic Nerve and Visual Alterationsmentioning
confidence: 69%
See 2 more Smart Citations